TMEM59 Haploinsufficiency Ameliorates the Pathology and Cognitive Impairment in the 5xFAD Mouse Model of Alzheimer’s Disease - Meng, Jian; Han, Linkun; Zheng, Naizhen; Xu, Hui; Liu, Zhaoji; Zhang, Xian; Luo, Hong; Can, Dan; Sun, Hao; Xu, Huaxi; Zhang, Yun-wu (Frontiers in Cell and Developmental Biology, 2020)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease associated with cognitive deficits and synaptic impairments. Amyloid-β (Aβ) plaque deposition, dystrophic neurite accumulation and neurofibrillary tangles are pathological hallmarks of AD. TMEM59 has been implicated to play a role in AD pathogenesis; however, the underlying mechanism remains unknown. Herein, we found that overexpression of TMEM59 in the hippocampal region led to memory impairment in wild type mice, suggesting its neurotoxic role. Interestingly, while TMEM59 overexpression had no effect on worsening synaptic defects and impaired memory in the 5xFAD mouse model of AD, it significantly exacerbated AD-like pathologies by increasing levels of detergent-insoluble Aβ and Aβ plaques, as well as dystrophic neurites. Importantly, haploinsufficiency of TMEM59 reduced insoluble Aβ levels, Aβ plaques, and neurite dystrophy, thereby rescuing synaptic plasticity and memory deficits in 5xFAD mice. Moreover, the level of TMEM59 in the brain of 5xFAD mice increased compared to wild type mice during aging, further corroborating its detrimental functions during neurodegeneration. Together, these results demonstrate a novel function of TMEM59 in AD pathogenesis and provide a potential therapeutic strategy by downregulating TMEM59.